2000
DOI: 10.1089/10445490050043344
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Encoding the 17-kDa Antigen ofBartonella henselaeis Located within a Cluster of Genes Homologous to thevirBVirulence Operon

Abstract: A Bartonella henselae genomic A library was screened with antiserum generated in mice against live B. henselae. One of the immunoreactive clones expressed a 17-kDa antigen that was characterized previously as an immunodominant protein of B. henselae. Sequence analysis of the recombinant clone, pBHIM-2, revealed that the open reading frame (ORF) encoding the 17-kDa antigen was situated between homologs of virB4 and virB6, two genes that belong to the virB operon. The virB operon has been associated with the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 22 publications
0
46
0
1
Order By: Relevance
“…Genetic comparison of this locus revealed that the 17kDa protein it encoded was a VirB5 homolog and further exploration of the locus revealed the presence of homologs of other members of the T4SS upstream and downstream of VirB5 [44,45]. The putative promoter region of the operon was also identified and its expression was shown to be induced when B. henselae was cultivated with human microvascular endothelial cells [46].…”
Section: Step 1: Infection Prior To Bacteraemiamentioning
confidence: 99%
“…Genetic comparison of this locus revealed that the 17kDa protein it encoded was a VirB5 homolog and further exploration of the locus revealed the presence of homologs of other members of the T4SS upstream and downstream of VirB5 [44,45]. The putative promoter region of the operon was also identified and its expression was shown to be induced when B. henselae was cultivated with human microvascular endothelial cells [46].…”
Section: Step 1: Infection Prior To Bacteraemiamentioning
confidence: 99%
“…They bear Walker A (motif I) and B (motif II or DExx box) NTP-binding sequences [88] and may use the energy of Rhizobium etli bacterium; N2-fixation [154] Sinorhizobium meliloti bacterium; N2-fixation [14,15,17] Shigella flexneri plasmid ColIb P9 bacterium; diarrhoea / dysentery [155] Bartonella henselae and tribocorum bacterium; cat scratch disease, bacteremia [156][157][158][159][160] Campylobacter jejuni bacterium; bacterial diarrhoea [161,162] Toxoplasma gondii protozoon; toxoplasmosis (encephalitis) [54] Leishmania donovani protozoon; leishmaniasis [54] Mycobacterium tuberculosis bacterium; tuberculosis [54] Bordetella bronchiseptica bacterium; bronchitis [14,15,17] Enterobacter aerogenes bacterium; nosocomial infections [11] Actinobacillus actinomycetemcomitans bacterium; periodontitis [14,15,17,163,164] Escherichia coli bacterium; diarrhea [11] Caulobacter crescentus bacterium; non-pathogenic [14,15,17] Coxiella burnetii bacterium; acute febrile disease, endocarditis, pneumonitis [165,166] Thiobacillus ferroxidans bacterium; iron oxidation [14,15,17] Wolbachia intracellular symbiont of arthropods; sexual alterations in host [167,168] Ralstonia eutrophantus bacterium; heavy-metal resistance [11,169] Salmonella typhi, typhimurium and enteriditis bacterium; typhus, salmonellosis …”
Section: Transfer Factors In Conjugative Type-iv Secretionmentioning
confidence: 99%
“…The pathogens utilizing type IV systems during infection include Helicobacter pylori (12), Bordetella pertussis (3), Brucella spp. (31, 42), Bartonella henselae (35,40), and Legionella pneumophila (47). A type IV system of H. pylori exports CagA to the cytosol of mammalian cells (32,41,44), whereas a related system exports pertussis toxin across the outer membrane of B. pertussis (3).…”
mentioning
confidence: 99%